2020
DOI: 10.17269/s41997-020-00417-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex, gender and COVID-19: a call to action

Abstract: An understanding of the influence of sex (biological attributes) and gender (socially constructed roles, behaviours, expressions, identities) factors on the risk of infection, hospitalization and death is of urgent importance in the COVID-19 pandemic response effort. Despite similar global rates of infection with Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2, the virus responsible for the COVID-19 pandemic), hospitalizations and mortality are higher in men than in women. Females may be less vulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 13 publications
3
57
0
Order By: Relevance
“…Eighty-three male patients were enrolled on the present study (58.5% of total): this data is consistent with the higher rates of hospitalization for COVID-19 infection in men than in women [13,14]. Most of them were overweight or obese.…”
Section: Discussionsupporting
confidence: 85%
“…Eighty-three male patients were enrolled on the present study (58.5% of total): this data is consistent with the higher rates of hospitalization for COVID-19 infection in men than in women [13,14]. Most of them were overweight or obese.…”
Section: Discussionsupporting
confidence: 85%
“…About four-fifths of both male and female undergraduates reported that they cover their noses when sneezing, another vital precautionary behavior promoted by the government. Overall, male undergraduates were less likely to report protective actions against COVID-19, as observed in some other studies [ 24 , 26 ]. Young male undergraduates’ cultural and religious norms and beliefs, as well as their active lifestyles, may have influenced them in not adhering to personal protective measures against COVID-19 that seem to restrict their freedom.…”
Section: Discussionsupporting
confidence: 74%
“…Gender has been identified as a vital factor that needs to be considered in any health promotion activity. COVID-19-related safety practices promoted by international health agencies have been criticized due to their cultural insensitivity and implementation issues in non-Western societies where gender plays a major role [ 24 , 25 ]. Although hand hygiene practices and covering the nose when sneezing were prevalent behaviors in Western societies even before the pandemic, such practices were not as common in non-Western societies, especially among people in poor socio-economic brackets.…”
Section: Discussionmentioning
confidence: 99%
“…Also, as increased mortality risk is associated with cardiovascular diseases (Yang et al, 2020), the greater percentage of these disorders and thrombosis in men may contribute to fatality increase among males. A higher case fatality rate could also result from the fact that in general, among intubated patients, men are more likely to acquire ventilator-associated pneumonia (Cook et al, 1998, Ahmed, Dumanski, 2020).…”
Section: Discussionmentioning
confidence: 99%